Attitudes toward feminism in older and younger adults: the influence of religiosity, political orientation, gender, education, and family - Fitzpatrick, Kathryn, author; Vacha-Haase, Tammi, advisor (Colorado State University. Libraries, 2009)
The purpose of the present study was to investigate attitudes toward feminism in a population of older and younger adults who were connected to each other through a family relationship (e.g., parent, grandparent). Using a database collected during the spring of 2007 which included 245 Introduction to Psychology students and 245 paired older adult family members, the influence of family, political affiliation, religiosity, education, and gender was explored. Participants completed an attitudes towards feminism scale, a political affiliation scale, a religiosity measure, and a demographic questionnaire. Results indicated that older adults were more conservative than younger adults on the attitudes towards feminism, religiosity, and political orientation measures. In young adults, attitudes towards feminism was predicted by gender and political orientation. In older adults, religiosity and political orientation were the best predictors. Looking at the influence between the generations, it was found that older adults' attitudes and demographic information were not associated with younger adults' attitudes towards feminism and the women's movement when the young adults' variables were controlled. In contrast, young adults' political views were associated with older adults' attitudes towards feminism when the older adults' variables were controlled. Findings highlight the importance of continuing to explore a bidirectional model of socialization.
Keywords: family; feminism; gender; older adults; political orientation; religiosity; religion; gerontology; social psychology; women's studies; individual and family studies